Macquarie PEN anthology of Aboriginal literature - Heiss, Anita, 1968-; Minter, Peter, 1967-; Jose, Nicholas, 1952- (Crows Nest, N.S.W. : Allen & Unwin, 2008)
Includes work produced in English by Australian Aboriginal authors published up to 2006.
Includes index.
" Macquarie PEN Anthology of Australian Literature, a companion volume to follow this work." -- Preface
" Published as part of the Macquarie PEN Anthology of Australian Literature Project. The project began with the Sydney Centre of International PEN, a world association of writers ..." -- Preface
Includes bibliographies.
Keywords: Australian literature -- Aboriginal Australian authors; Aboriginal Australians -- Social life and customs; Aboriginal Australians -- History; Literature and stories - Authors; Literature and stories; History - Biographies